New genera of Afrotropical limosinine sphaerocerids (Diptera: Sphaeroceridae) - Papp, László (Zootaxa, 2014)
Eight new genera of the subfamily Limosininae are described from the Afrotropical region: Afrolimosina gen. n. (type species A. albitarsis sp. n.), Biphallapodema gen. n. (type species B. polydentata sp. n., additional species B. oligodentata sp. n.), Chelilimosina gen. n. (type species Ch. baloghi sp. n.), Mislocatus gen. n. (type species Ceroptera ealensis Vanschuytbroeck, 1951), Oligochaetosella gen. n. (type species O. inconspicua sp. n.), Permixtolimosina gen. n. (type species P. sexsetosa sp. n.), Preepiphallus gen. n. (type species P. nitidifacies sp. n., additional species P. endrodyi sp. n.), Subacuminiseta gen. n. (type species S. minor sp. n.). Comparisons to the key for the identification of Old World genera of Limosininae (Papp 2008) are given. With 118 original figures.